Information Provision for Informed Prenatal Decision Making - Burkell, Jacquelyn; McKenzie, Pamela J. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
In decision making in maternity care, midwives provide information to support client-centred decisions. Although midwives are expected to maintain neutrality, a variety of concerns limit nondirectiveness. The impact of these concerns is explored through qualitative analysis of midwife-client interactions. The results provide insight into what counts as “information” in these interactions. Lors de la prise de décision dans les soins de maternité, les sages-femmes offrent des informations pour soutenir les décisions de leurs patientes. Bien que l’on suppose que les sages-femmes doivent conserver une certaine neutralité, de nombreuses préoccupations limitent le manque de directives. L’impact de ces préoccupations est exploré à travers une analyse qualitative des interactions entre sages-femmes et patientes. Les résultats présentent un aperçu de ce qui est considéré comme « information » dans ces interactions.